2016
DOI: 10.1021/acs.chemmater.6b00430
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Properties, and Applications of Transition Metal-Doped Layered Transition Metal Dichalcogenides

Abstract: Research into layered transition metal dichalcogenides (TMDCs), most notably those of molybdenum and tungsten disulfides, has become extensive, involving fields as diverse as optoelectronics, spintronics, energy storage, lubrication, and catalysis. The modification of TMDCs by transition metal doping can improve their performance in such applications and hence extend their potential for technological applications. This review concerns the synthetic strategies that have been used to incorporate transition metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
335
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 485 publications
(343 citation statements)
references
References 71 publications
6
335
0
2
Order By: Relevance
“…[56] Despite testing a range of deposition conditions, for example, temperatures from 150 to 500 °C, we either obtained no films at all or the films were highly nonuniform in thickness across the substrates. Increasing the MoCl 5 dose decreased the film thickness close to the precursor inlet, which hints toward etching of the deposited film by MoCl 5 . Later, we also found that Mo(CO) 6 , the other molybdenum precursor used for ALD of MoS 2 , [47][48][49][50][51][52] suffered from heavy precursor decomposition in our reactor already at 110 °C.…”
Section: Evaluation Of Published Mos 2 Processesmentioning
confidence: 90%
See 1 more Smart Citation
“…[56] Despite testing a range of deposition conditions, for example, temperatures from 150 to 500 °C, we either obtained no films at all or the films were highly nonuniform in thickness across the substrates. Increasing the MoCl 5 dose decreased the film thickness close to the precursor inlet, which hints toward etching of the deposited film by MoCl 5 . Later, we also found that Mo(CO) 6 , the other molybdenum precursor used for ALD of MoS 2 , [47][48][49][50][51][52] suffered from heavy precursor decomposition in our reactor already at 110 °C.…”
Section: Evaluation Of Published Mos 2 Processesmentioning
confidence: 90%
“…In monolayer MoS 2 (thickness ≈0.6 nm), the band gap becomes direct with a width of 1.8 eV. [1] Importantly, to meet the requirements of different applications, properties of MoS 2 and other TMDCs can be tuned by controlling the thickness, [1] doping and alloying, [5][6][7][8] surface modification and functionalization, [9][10][11] strain, [12,13] and by creating heterostructures with other 2D materials. [6,[14][15][16] The appealing properties of TMDCs have led to a wide range of proposed applications.…”
mentioning
confidence: 99%
“…¥ÑÒËÓÑÄÂÐËÇ ÔÕÓÖÍÕÖÓ ÂÕÑÏÂÏË V ÅÓÖÒÒÞ (V, Nb) ÒÓËÄÑAEËÕ Í ÖÄÇÎËÚÇÐËá àÎÇÍÕÓËÚÇÔÍÑÌ ÒÓÑÄÑAEËÏÑÔÕË Ë ÍÑÐÙÇÐÕÓÂÙËË ÐÑÔËÕÇÎÇÌ ÊÂÓâAEÑÄ Ä ¥±®-ÏÂÕÇÓËÂÎÂØ Ä 20 Ë 40 ÓÂÊ ÔÑÑÕÄÇÕÔÕÄÇÐÐÑ [166,167].…”
Section: à2unclassified
“…The representative atomic structures of some 2D materials are shown in Fig. 1 (Tedstone et al, 2016). TMDs are generally denoted as MX 2 , where M is the transition metal (Mo, W, Ti, V, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…and X is a chalcogen (S, Se, Te, etc. ); these atoms are layered as X-M-X units by van der Waals bonding (Tedstone et al, 2016). Theoretically, there are 88 combinations of TMDs, but it was discovered using density functional theory (DFT) that only 44 stable monolayer or few-layer TMDs can exist stably (Ataca et al, 2012).…”
Section: Introductionmentioning
confidence: 99%